Assessment of Trans Fatty Acid and Conjugated Linoleic Acid Content of Turkish Commercial Ice Creams - Selim Cakmak, Yavuz; Zengin, Gokhan; Akkoyunlu, Nurkan; Aktumsek, Abdurrahman; Ozmen Guler, Gokalp (Asian Journal of Chemistry, 2012)
In this study, 27 commercial ice creams belonging to 4 different brands sold in Turkey were analyzed for their fatty acid composition, with relevance on their trans fatty acid and conjugated linoleic acid content. 16:0 palmitic acid was major fatty acid in all samples, except for cacao and chocolate ice creams. Other predominant fatty acids were 12:0 lauric acid, 18:0 stearic acid and 18:1 w9 oleic acid. Saturated fatty acids occurred in the largest proportions in all samples followed by monounsaturated fatty acids and polyunsaturated fatty acids. The total percentages of saturated fatty acids, monounsaturated fatty acids and polyunsaturated fatty acids ranged between 61.56-80.99, 13.30-30.86 and 3.68-8.02 %, respectively. Trans fatty acids and conjugated linoleic acid contents in ice cream samples were between 0.71-2.66 and 0.17-0.91 %, respectively. The results of this research have demonstrated that trans fatty acid and conjugated linoleic acid contents of ice creams obtained in Turkey are favorable levels when compared to many countries.